Short-term outcomes of robotic- versus laparoscopic-assisted Total Gastrectomy for advanced gastric Cancer: a propensity score matching study - Changdong Yang (BMC Cancer, 2020)
Abstract Background Few studies have been designed to evaluate the short-term outcomes between robotic-assisted total gastrectomy (RATG) and laparoscopy-assisted total gastrectomy (LATG) for advanced gastric cancer (AGC). The purpose of this study was to assess the short-term outcomes of RATG compared with LATG for AGC. Methods We retrospectively evaluated 126 and 257 patients who underwent RATG or LATG, respectively. In addition, we performed propensity score matching (PSM) analysis between RATG and LATG for clinicopathological characteristics to reduce bias and compared short-term surgical outcomes. Results After PSM, the RATG group had a longer mean operation time (291.14 ± 59.18 vs. 270.34 ± 52.22 min, p = 0.003), less intraoperative bleeding (154.37 ± 89.68 vs. 183.77 ± 95.39 ml, p = 0.004) and more N2 tier RLNs (9.07 ± 5.34 vs. 7.56 ± 4.50, p = 0.016) than the LATG group. Additionally, the total RLNs of the RATG group were almost significantly different compared to that of the LATG group (34.90 ± 13.05 vs. 31.91 ± 12.46, p = 0.065). Moreover, no significant differences were found between the two groups in terms of the length of incision, proximal resection margin, distal resection margin, residual disease and postoperative hospital stay. There was no significant difference in the overall complication rate between the RATG and LATG groups after PSM (23.8% vs. 28.6%, p = 0.390). Grade II complications accounted for most of the complications in the two cohorts after PSM. The conversion rates were 4.55 and 8.54% in the RATG and LATG groups, respectively, with no significant difference (p = 0.145), and the ratio of splenectomy were 1.59 and 0.39% (p = 0.253). The mortality rates were 0.8 and 0.4% for the RATG and LATG groups, respectively (p = 1.000). Conclusion This study demonstrates that RATG is comparable to LATG in terms of short-term surgical outcomes.